2005
DOI: 10.1027/0269-8803.19.4.256
|View full text |Cite
|
Sign up to set email alerts
|

Mediofrontal Negativities to Averted Gains and Losses in the Slot-Machine Task

Abstract: In a previous study we addressed the question whether a feedback-related negativity (FRN) can be elicited by outcomes that are not contingent on any preceding choice or action ( Donkers, Nieuwenhuis, & Van Boxtel, 2005 ). Participants took part in a simple slot-machine task in which they experienced monetary gains and losses in the absence of responses. In addition, they performed a time estimation task often used to study the FRN, and a flanker task known to elicit the error-related negativity (Ne/ERN). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 16 publications
8
37
0
Order By: Relevance
“…This lesser commitment may produce the FRN with some variation or reduction. Such interpretation implies that the reinforcement learning theory of FRN needs to be extended not only to learning that is not specifically related to recently executed actions [8,9], but also to learning that is based on expectation about the future. Specifically, knowing that something bad is about to happen, even though this bad thing can be avoided, is sufficient for the basal ganglia to update its predictions and to send the phasic dopamine signals to the anterior cingulate cortex, which generates the FRN.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This lesser commitment may produce the FRN with some variation or reduction. Such interpretation implies that the reinforcement learning theory of FRN needs to be extended not only to learning that is not specifically related to recently executed actions [8,9], but also to learning that is based on expectation about the future. Specifically, knowing that something bad is about to happen, even though this bad thing can be avoided, is sufficient for the basal ganglia to update its predictions and to send the phasic dopamine signals to the anterior cingulate cortex, which generates the FRN.…”
Section: Discussionmentioning
confidence: 98%
“…One particular issue that could have important implications for the reinforcement learning theory concerns whether the FRN is only elicited by negative outcomes experienced by participants of a study and whether these outcomes should be contingent upon recent actions: if the FRN reflects a process of performance monitoring and/or learning about recently executed actions, then it should be observed only when negative outcomes are experienced with respect to response choices. Two recent studies, however, demonstrated that the FRN can be elicited in simple monetary gambling tasks in which participants make no active choices and no overt actions [8,9]. This finding has been taken to suggest that the FRN reflects an evaluation of the motivational impact of outcomes and as such is associated with feedback signals in general instead of with feedback signals specifically related to recently executed actions.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…To our knowledge, although some studies have attempted to examine positive feedback effects (Donkers and van Boxtel, 2005), there are only two that tried to avoid the confound between expectancy and valence. Oliveira and colleagues (2007) asked their participants to estimate the time when a moving light would reach a covered target position and, after that, to judge the accuracy of their own estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Holroyd, Krigolson, Baker, Lee, & Gibson, 2009;Krigolson, Pierce, Holroyd, & Tanaka, 2009;Walsh & Anderson, 2012). However, several studies in the last ten years have provided evidence that the FRN conveyed an unsigned prediction error or ''salience" encoding signal (Donkers, Nieuwenhuis, & Van Boxtel, 2005;Hauser et al, 2014;Oliveira, McDonald, & Goodman, 2007;Talmi, Atkinson, & El-Deredy, 2013). More recently, Sambrook and Goslin (2015) utilized the ''great grand averages" approach in a meta-analysis study and showed strong effects of magnitude and likelihood on the FRN, which provided new evidence to support the RL_ERN theory.…”
Section: Introductionmentioning
confidence: 85%